2023
DOI: 10.1108/md-02-2022-0136
|View full text |Cite
|
Sign up to set email alerts
|

Influence of augmented reality on shopping behavior

Abstract: PurposeDigital technologies emerged as innovative avenues for launching new products, advertising brands, increasing customer awareness and thus leaving a remarkable impact on the online marketplace. The present study analyzed the effects of crucial antecedents of AR interactive technology on customers' behavior toward AR-based e-commerce websites.Design/methodology/approachConvenience sampling was used to collect primary data from 357 iGen respondents aged 16–22 years; residing in New Delhi and the NCR region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(3 citation statements)
references
References 143 publications
0
3
0
Order By: Relevance
“…Perceived enjoyment is one of the intrinsic motivation factors that can affect the attitude, intention, and behavior of consumers towards online shopping. Perceived enjoyment can be measured by indicators such as pleasure, interest, and excitement of using online shopping website or application [5]. On the studies by Rahmi et al, (2022), which found that perceived risk influences perceived enjoyment, with gamification and access-based consumption as moderating variables11.…”
Section: Perceived Enjoymentmentioning
confidence: 99%
“…Perceived enjoyment is one of the intrinsic motivation factors that can affect the attitude, intention, and behavior of consumers towards online shopping. Perceived enjoyment can be measured by indicators such as pleasure, interest, and excitement of using online shopping website or application [5]. On the studies by Rahmi et al, (2022), which found that perceived risk influences perceived enjoyment, with gamification and access-based consumption as moderating variables11.…”
Section: Perceived Enjoymentmentioning
confidence: 99%
“…Gender as a moderator has been investigated in advertising and consumer behavior research (Dogra et al, 2023;Khan & Rahman, 2016).…”
Section: Gender As a Moderatormentioning
confidence: 99%
“…VR, on the other hand, creates entirely virtual environments, allowing businesses to transport consumers to simulated settings where they can experience products or services firsthand [34,35]. These technologies have the potential to enhance product demonstrations, provide virtual tours, and facilitate try-before-you-buy experiences on a global scale [36][37][38].…”
Section: Augmented Reality and Virtual Realitymentioning
confidence: 99%